Teachers women in the coordination of the Bachelor of Science and Technology: between achievements and challenges (Research, Society and Development, 2019)
The origin of the Bachelor of Science and Technology of the Federal University of Rio Grande do Norte (UFRN) is closely related to the Program to Support Restructuring and Expansion Plans of Federal Universities (REUNI) that took place in Brazilian federal public universities in 2008 Throughout the history of the baccalaureate it is possible to see the expansion of the spaces of participation of the female teachers in the functions of leadership and management. So, the objective of the present study is to investigate the female presence during the 10 years of the Bachelor of Science & Technology in front of the course coordination emphasizing achievements and challenges. With regard to methodology, it can be said that this is a qualitative research of a historical character with a biographical approach, which makes use of narratives and the analytical strategy of immersion and hermeneutic contemplation. As for the methodological procedures, two sources are used for the collection of empirical material: documentary source with the analysis of the Political Project Pedagogical of the Bachelor and the Internal Regiment of the School of Sciences & Technology and; empirical source with the accomplishment of narrative interviews to know the achievements and challenges through the lines of the teachers who worked / work in the coordination of the course. Finally, the study evidenced the process of feminization of management personnel at UFRN, in particular the coordination of the Bachelor of Science and Technology, the major undergraduate course in the State of Rio Grande do Norte.